‘INIAP-Palmira 2014’: a new drought-resistance barley variety (2015)
Barley (Hordeum vulgare L.) is produced in the Ecuadorian highlands ( 3,000 m a.s.l.) primarily for self-consumption and small-scale commercialization. Not many crop species are adapted to this altitude; therefore, barley is one of a few crop species that can be grown at these locations. Severe environmental conditions can be found in the Ecuadorian highlands since the region is characterized by poor soils and water deficiency ( 300 mm yearsup-1). The Instituto Nacional de Investigaciones Agropecuarias (INIAP) has developed ‘INIAP-Palmira 2014’, a hulled two-row barley variety adapted to Ecuadorian agricultural conditions in the highlands. ‘INIAP-Palmira 2014’ showed acceptable yield performance as compared with the most popular improved barley cultivars in different production areas located in Ecuador. However, this new barley variety showed superior performance under water stress conditions in the highlands highlands (3.000 m a.s.l.). Additionally, ‘INIAP-Palmira 2014’ showed disease resistance, mainly to yellow rust, in all of the locations where the new variety was evaluated.